Exploring cultural inclusion: Perspectives from a community arts organisation. (May 2015) - Azmat, Fara; Fujimoto, Yuka; Rentschler, Ruth
Using focus group interviews and individual stories of participants from secondary data, we illuminate the role of Multicultural Arts Victoria (MAV) in Australia in how it promotes cultural inclusion through programs of social and civic service. Our findings confirm the significance of cultural inclusion and the potentially useful role of arts in creating inclusive organisations and communities. We further develop a framework of cultural inclusion in the workplace to provide a holistic understanding of the cultural inclusion process that can lead to the development of inclusive workplaces. As social inclusion is central to Australia's national identity, this article helps researchers and practitioners to understand how cultural inclusion and inclusive organisational theories collide and complement each other to create inclusive organisations.